LEGIFERAREA ȘI FUNCȚIA LEGISLATIVĂ A PARLAMENTULUI - Arnăut, Veronica (SUPREMANCE OF LAW, 2017)
The article includes a study of lawmaking as a distinct activity in the state in order to clarify its essence and to concretize the legislative function of the Parliament as the sole legislative authority of the state. There are analyzed the concepts of „legislative function” and „legislative competence” and the distinction between them.
Keywords: lawmaking; legislative activity; Legislative function; Parliament